'Knowledge capital' and innovation in global corporations. (8th February 2007) - Laperche, Blandine
Currently, the formation and the protection of a knowledge base is of major importance to firms. In this paper, we explain the formation of the firm's 'knowledge capital'. We develop the idea of the existence of a growing contradiction between, on the one hand, the socialisation of the 'knowledge capital', and, on the other hand, the tendency toward its oligopolistic appropriation, which is made easier notably by the evolution of patent laws and practices. This contradiction can be explained by today's profitability imperative and its related necessity to reduce the risk for the cost and the length of technological progress.